Evaluating the core microbiota in complex communities: A systematic investigation. (10th February 2017) - Astudillo‐García, Carmen; Bell, James J.; Webster, Nicole S.; Glasl, Bettina; Jompa, Jamaluddin; Montoya, Jose M.; Taylor, Michael W.
Summary: The study of complex microbial communities poses unique conceptual and analytical challenges, with microbial species potentially numbering in the thousands. With transient or allochthonous microorganisms often adding to this complexity, a 'core' microbiota approach, focusing only on the stable and permanent members of the community, is becoming increasingly popular. Given the various ways of defining a core microbiota, it is prudent to examine whether the definition of the core impacts upon the results obtained. Here we used complex marine sponge microbiotas and undertook a systematic evaluation of the degree to which different factors used to define the core influenced the conclusions. Significant differences in alpha‐ and beta‐diversity were detected using some but not all core definitions. However, findings related to host specificity and environmental quality were largely insensitive to major changes in the core microbiota definition. Furthermore, none of the applied definitions altered our perception of the ecological networks summarising interactions among bacteria within the sponges. These results suggest that, while care should still be taken in interpretation, the core microbiota approach is surprisingly robust, at least for comparing microbiotas of closely related samples.